PREPARATION FOR FEDERAL HEARINGS (Tufts Archival Research Center, 2007)
Guide for federal hearings regarding excise taxes, public smoking and advertising restrictions. Gives the background on the subject and then details the strategy to be employed by the tobacco industry to fight the legislation. Focuses on reframing the issue in order to make it less damaging to the tobacco industry.